Effect of phase change materials on building heating and cooling load considering different wall combinations - Özdemir, Mustafa; Gulten, Ayca (My University, 2024)
In this study, energy analyzes were carried out on a sample building for wall types where 3 main materials (brick, concrete block, aerated concrete) and 3 different insulation materials were used in different combinations, taking into account the situations with and without PCM. Building heating and cooling loads for 39 different scenarios derived in this way were determined by taking into account the coldest and hottest days of the year and also as the total energy need during the year. Analyzes were made with the Design Builder program and the results are presented with tables and graphs. By comparing and classifying the total energy loads of wall samples created for 39 different scenarios during the year, wall types that gave more positive results were determined. Three different PCM types with melting temperatures of 21 °C, 23 °C and 29 °C were used in the analyses. Based on the main material of the wall, three walls with the best performance among their main materials were initially determined. Then, among the wall types consisting of these 3 main materials (brick, concrete block, aerated concrete), the walls that showed the best performance were determined among the combinations created with the addition of insulation material and PCM. According to the results of the simulations, 25% energy savings were achieved when only insulation materials (XPS, EPS, Rock Wool) were used in the building envelope, and 9% energy savings were achieved when only PCM was used. By using PCM and insulation materials (XPS, EPS, Rock Wool) together, 30% energy savings were achieved.
Keywords: Energy analysis; phase change material; design builder; cooling load analysis; heating load analysis; building envelope; simulatio